A comparative study between Chinese propolis and Brazilian green propolis: metabolite profile and bioactivity. Issue 3 (4th March 2020) - Yuan, Min; Yuan, Xu-jiang; Pineda, Miguel; Liang, Ze-yu; He, Jian; Sun, Sheng-wei; Pan, Tian-ling; Li, Kun-ping
Abstract : A comparative study between Chinese propolis and Brazilian green propolis showed that they have a distinct chemome but similar antioxidant and anti-inflammatory potential. Abstract : Among different types, Chinese propolis (ChPs) and Brazilian green propolis (BrGPs) have been shown to contain multi-functional properties. Despite extensive research in the field, reports comparing propolis from different geographical areas are still limited, compromising our current understanding of the potential therapeutic effect associated with propolis and its derived compounds. Herein, a comparative study between ChPs and BrGPs including their metabolite profile and bioactivities was performed. Interestingly, even when ChPs and BrGPs showed similar anti-inflammatory potential, our results showed that they contained very different levels of ethanol extract, total flavonoids and total phenolic acids and in fact, LC-MS metabolic profiling and pattern recognition could effectively distinguish ChPs and BrGPs. Moreover, all the propolis samples tested showed good anti-oxidant activity and no significant difference of free radical scavenging capacity existed between ChPs and BrGPs. In conclusion, ChPs and BrGPs have a distinct chemome, but their antioxidant and anti-inflammatory activities are similar.